The social play, social skills and parent–child relationships of children with ADHD 12 months following a RCT of a play-based intervention - Barnes, G.; Wilkes-Gillan, S.; Bundy, A.; Cordier, Reinie (Wiley-Blackwell Publishing Asia, 2017)
© 2017 Occupational Therapy Australia Background/aim: There is an urgent need to investigate the long-term impact of social skill interventions for children with attention deficit hyperactivity disorder (ADHD). Interventions targeting the social skills of children with ADHD have limited short-term effectiveness and rarely investigate the long-term impact. Furthermore, these interventions are most frequently conducted in the clinic setting, without including the child's natural settings and interactants, such as their regular playmates and parents. Methods: The present study investigated the social play, social skills and parent–child relationships of children with ADHD and their playmates (n = 13/group) aged 5–13 years. A two-group before and after design with a longitudinal component was applied. Participant data compared over two time points, immediately following a randomised, controlled trial (RCT) of a play-based intervention and 12 months post-RCT. Results: From immediately following the RCT to the 12-month follow-up, children with ADHD maintained social play skill gains in the home environment. Playmates maintained social play skill gains across the home and clinic environments. Children scored within a developmentally appropriate range, falling within 1 standard deviation of the mean for social skills and most parent–child relationship scales using norm-based assessments. Conclusion: Results support the long-term effectiveness of the intervention.